Research on Non-rigid Structure from Motion: A Literature Review (Journal of Fiber Bioengineering and Informatics, 2015)
Non-rigid Structure from Motion (NRSfM) is a classical computer vision problem. And the main methods\rused to solve it are in general based on shape models or trajectory models. This paper will provide an\roverview over kinds of solutions proposed in these researches. It not only gives out the theoretical\rinsights proposed by researchers in recent years, but also discusses them with their pros and cons. At\rthe same time, the progress of the research about this topic is described in detail and its long-term trend\ris introduced at the end. This paper is very easy to understand, which mainly introduces two practical,\reveryday models for the NRSfM problem, namely trajectories based model and shape based model. Both\rof them are based on matrix factorization technology. Inevitably, some relevant optimization methods\rare mentioned to solve the projection matrix and corresponding coefficients effectively.
Keywords: Non-rigid Structure From Motion; Optimization Methods; Shape Models; Matrix Factorization; Trajectory Basis; Discrete Cosine Transform